Graphene network enabled high speed electrical actuation of shape memory nanocomposite based on poly(vinyl acetate). Issue 5 (14th December 2016) - Sabzi, Mohammad; Babaahmadi, Masoud; Samadi, Navid; Mahdavinia, Gholam Reza; Keramati, Mohsen; Nikfarjam, Nasser
Abstract: Here strong electroactive shape memory nanocomposites were prepared by incorporating graphene nanoplatelets into poly(vinyl acetate) (PVAc) through the simple solvent mixing method. TEM and XRD revealed that well exfoliated graphene nanoplatelets formed a continuous network throughout the matrix with a large amount of interconnectedness. Dynamic mechanical analysis showed that the inclusion of graphene significantly improves both glassy and rubbery moduli of the matrix. Furthermore, the prepared nanocomposites demonstrated a marked electrical conductivity up to 24.7 S m −1 and thereby surprisingly rapid electrical actuation behaviour exhibiting a 100% recovery ratio in 2.5 s. Moreover, PVAc and its nanocomposites displayed scratch self‐healing capability. This work demonstrates that the PVAc/graphene nanocomposites with high modulus and excellent electroactive shape memory performance can be a promising material in many applications such as sensors and fast deployable and actuating devices. © 2016 Society of Chemical Industry Abstract : Strong electroactive shape memory nanocomposites were prepared by incorporating graphene nanoplatelets into poly(vinyl acetate) (PVAc) through the simple solvent mixing method. Dynamic mechanical analysis showed that the inclusion of graphene significantly improves both glassy and rubbery moduli of the matrix. Furthermore, the prepared nanocomposites demonstrated a marked electrical conductivity up to 24.7 S m −1 and surprisingly rapid electrical actuation behavior exhibiting a 100% recovery ratio in 2.5 s. This work demonstrates that PVAc/graphene nanocomposites with high modulus and excellent electroactive shape memory performance can be a promising material in many applications such as sensors and fast deployable and actuating devices.